For instance the accelerated series
\begin{equation*}
\zeta (3)=\sum_{n=1}^{\infty }\frac{1}{n^{3}}=\frac{5}{2}\sum_{1}^{\infty }
\frac{(-1)^{n-1}}{n^{3}\dbinom{2n}{n}}
\end{equation*}
can be obtained by letting $N\rightarrow \infty $ in
\begin{equation*}
\sum_{n=1}^{N}\frac{1}{n^{3}}-2\sum_{n=1}^{N}\frac{\left( -1\right) ^{n-1}}{n^{3}\binom{2n}{n}}=\sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{N+k}{k}\binom{N}{k}}-\sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{2k}{k}}.
\end{equation*}
\begin{equation*}
\zeta (3)=\sum_{n=1}^{\infty }\frac{1}{n^{3}}=\frac{5}{2}\sum_{1}^{\infty }
\frac{(-1)^{n-1}}{n^{3}\dbinom{2n}{n}}
\end{equation*}
can be obtained by letting $N\rightarrow \infty $ in
\begin{equation*}
\sum_{n=1}^{N}\frac{1}{n^{3}}-2\sum_{n=1}^{N}\frac{\left( -1\right) ^{n-1}}{n^{3}\binom{2n}{n}}=\sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{N+k}{k}\binom{N}{k}}-\sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{2k}{k}}.
\end{equation*}